Effects Of Recombinant Lactococcus Lactis And Bacteriocin Ul4 In The Protection Of Tilapia (Oreochromis Niloticus) Against Aeromonas Hydrophila - Karunakaramoorthy, Anuradha (2009)

(untitled)
The study was conducted to determine the effects of constructed recombinant Lactococcus lactis and bacteriocin UL4 for the protection of tilapia against Aeromonas hydrophila. For the constructions of recombinant L. lactis, a 250 bp domain 1 and 750 bp domain 4 of aerolysin produced by A. hydrophila were amplified by PCR and individually cloned into pNZ8048. The constructed plasmids, designated as pNHD1 and pNHD4, were then electrotransformed into Lactococcus lactis. Total RNA was then extracted and subjected to reverse transcriptase PCR. The agarose gel electrophoresis results showed the expected bands of pNHD1 and pNHD4 with 268 bp and 768 bp respectively. Subsequently, whole cell protein of recombinant L. lactis was extracted and separated by SDS-PAGE prior to Western blot analysis. The results of immunoblots using specific polyclonal antibodies showed that both domains 1 (~9 kDa) and 4 (~30 kDa) were successfully expressed in L. lactis. On the first fish trial, tilapia was injected intraperitoneally using recombinant L. lactis. Growth performance of tilapia with recombinant L. lactis was more profound and ELISA results showed a significantly higher antibody level (P<0.05) compared to control groups. The survival rate after challenge was more than 80 % for recombinant L. lactis groups, whereas only 60 % was observed for control group. Lactic acid bacteria (LAB) count of intestine digesta of fish that survived was maintained at high count (> 6 log cfu/ml) compared to control. On the other hand, the Enterobacteriaceae and A. hydrophila count were maintained at low count (< 6 log cfu/ml) after the trial. For the second trial, tilapia was orally immunized using recombinant L. lactis for four weeks. The growth performance of fish with recombinant L. lactis was more profound than control fish, even after challenged with A. hydrophila. Moreover, the antibody level increased significantly in week 2 in fish serum fed with recombinant L. lactis compared to control. The survival rate of tilapia after challenge was 100 % for recombinant L. lactis. The Enterobacteriaceae and A. hydrophila count of intestine digesta of survived fish was maintained at low count (< 5 log cfu/ml) compared to control, whereas the LAB count were maintained at more than 4 log cfu/ml. The best bacteriocin producer from six strains of L. plantarum isolated from local foods was identified and bacteriocin UL4 was selected based on antimicrobial activity determined by the diameter of the inhibition zone of A. hydrophila. Oral feeding was carried out and better growth performance was observed in bacteriocin UL4 fed tilapia compared to control. ELISA results showed the antibody level increased significantly in week 3 in fish serum fed with bacteriocin compared to control. The survival rate after challenge was 100 % and only 45 % for bacteriocin fed fish and control fish respectively. Enterobacteriaceae and A. hydrophila count of intestine digesta of survived fish maintained at low count (< 5 log cfu/ml) compared to control, whereas LAB count were maintained at high count (> 6 log cfu/ml). The results obtained in this study indicate the vast potential of recombinant L. lactis as a promising vaccine to prevent the infection of A. hydrophila particularly and generally to reduce the extensive use of antibiotics in controlling diseases and for the overall improvement of the health of fishes. The bacteriocin from LAB also showed good effects on the health improvement of fish and could be an ideal alternative to be used as a supplement for a general protection and prevention of diseases.